Home advantage perceptions in elite handball: a comparison among fans, athletes, coaches, and officials - Gershgoren, L.; Levental, O.; Basevitch, I. (Frontiers in Psychology, 2022)
Home advantage in sports has been extensively researched in the academic literature over the past five decades. A review of the literature reveals several factors that consistently underly this phenomenon. One of the most documented is the home crowd effect. While the crowd effect on the results has been widely researched considering noise, size, and density, there are conflicting findings of the effect and its extent. Furthermore, the perceptions of fans, athletes, coaches, and officials of the causes of home advantage in general and the crowd effect in particular, remain marginal. This is especially important in the face of significant regulation changes in the stands caused by the COVID-19 pandemic. The current study, therefore, examined the perceptions of fans, athletes, coaches, and officials of the Israeli handball premier league regarding fans` contribution to the home advantage phenomenon along with other factors (e.g., travel and officiating). A questionnaire examining perceptions regarding home advantage was distributed to 232 Israeli participants (117 fans, 59 players, 26 coaches, and 30 officials). Results, based on MANOVA, ANOVA, and post-hoc analyses, indicated significant differences in participants` perceptions of the different factors in general and the crowd factor in particular. Overall, the crowd was perceived as the most important factor contributing to the home advantage phenomenon (M = 5.7). Furthermore, fans perceived their contribution (i.e., the crowd) significantly higher than the rest of the participants (p = 0.001; i.e., players, coaches, and officials). On the other hand, officials ranked their contribution to the home advantage effect as low as well as significantly under ranked their contribution in comparison to the other groups (p < 0.001). This result suggests that officials perceive themselves as relatively robust to the crowd effect compared to the other participants. Additional results are discussed in light of existing gaps in the literature on the home advantage phenomenon. Alongside the theoretical contribution, these findings contribute to applied implications of increasing the home advantage effect when playing at home and negating the home advantage when playing away.